2015
DOI: 10.1111/jep.12401
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effectiveness and cost‐effectiveness of clinical nurse specialist‐led hospital to home transitional care: a systematic review

Abstract: There is low-quality evidence that CNS transitional care improves patient health outcomes, delays re-hospitalization and reduces hospital length of stay, re-hospitalization rates and costs. Further research incorporating robust economic evaluation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
121
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(141 citation statements)
references
References 47 publications
9
121
1
10
Order By: Relevance
“…However, another review found no difference in health outcomes due to preventative home visits [23]. Transitional support provided by clinical nurse specialists reduced re-hospitalizations [24]. Two reviews examined case management interventions (i.e., collaborative patient care to meet patients’ holistic needs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, another review found no difference in health outcomes due to preventative home visits [23]. Transitional support provided by clinical nurse specialists reduced re-hospitalizations [24]. Two reviews examined case management interventions (i.e., collaborative patient care to meet patients’ holistic needs).…”
Section: Resultsmentioning
confidence: 99%
“…Same effect sizes in studies of different quality.Home with supportMehta, 2011, [18]P: Patients who have had surgery for a hip fracture I: Home physiotherapy C: No physiotherapy and outpatient physiotherapy O: Indicators of health, quality of life, performance-based indicatorsHome physiotherapy was better than no physiotherapy care for improving patient-reported health-related quality of life.Cochrane risk of bias tool Overall moderate to low quality evidenceNo differenceTurner, 2011 [28]P: Older people living at home I: Modification of physical hazards in the home and related components (e.g., education) C: Usual care O: Injury rateThe effect of home modification on falls was either inseparable or insignificant.EPOC checklist Inclusion criteria limited to higher quality RCTs.Evidence was inseparable or insignificantFens, 2013, [19]P: Post-stroke older patients discharged home I: Multidisciplinary care including home assessment, assessment with follow-up care, education.C: Usual Care O: Indicators of health and well-beingLimited evidence for the effectiveness of multidisciplinary care for stroke patients being discharged home compared to usual care.CONSORT Studies ranged from 35% to 62%, with a mean of 50%No differenceYou, 2013 [25]P: Community- dwelling frail elders aged 65+ years I: Independent case management interventions applied in the community C: Usual care O: Health service useModerate evidence that case management interventions can improve clients’ use of some community care services and delays nursing home placement, reduces nursing home admission, and shortens length of nursing home stay.Used a checklist informed by evidence. Moderate and lower quality studies.Home with supportBryant-Lukosius, 2015 [24]P: Patients receiving care (subgroup analysis of elderly) I: Transitional support from a clinical nurse specialist C: Usual care O: Health system utilization, patient health outcomes, caregiver outcomesEvidence that clinical nurse specialist transitional support reduced re-hospitalizations and improved caregiver depression. The effects on other outcomes were less clear.Modified Cochrane risk of bias tool GRADE Moderate risk (n-3); high risk ( n  = 2) Low-quality evidence where GRADE could be appliedHome with supportReilly, 2015 [26]P: People with dementia living in the community and their carers I: Case management (planning and coordination of care) C: Usual care O: Health and health resource indicatorsSome evidence that case management is beneficial for improving some outcomes at certain time points, both in the person with dementia and in their caregiver.Cochrane risk of bias tool Low to moderate overall risk of biasHome with supportLiu, 2016 [27]P: Adults 60+ years with complex needs I: Supportive care environment at home, including technology use C: Usual care O: Aging in place indicators, technology readinessHome health monitoring technologies reduce some negative health outcomes for the elders,...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These non‐clinical domains are necessary to integrate all advanced practice activities, and could have an impact on the effectiveness of the roles (Bryant‐Lukosius, Beauchesne, Farrelly, & Murphy, ). The integration of these domains has demonstrated its effectiveness in improving health systems, patient outcomes, efficiency, and effectiveness (Bryant‐Lukosius et al, ; Donald et al, ). The development and implementation of APN affects healthcare delivery, organization, management, workforce planning, policy, and research outcomes (Andregård & Jangland, ), creating sustainable nursing services that meet the needs of the study context.…”
Section: Discussionmentioning
confidence: 99%
“…In Ireland, CNS roles developed in 2001 focusing on the core concepts of client focused, advocacy, audit/research, education/training and consultancy (National Council for the Professional Development of Nursing and Midwifery ). CNSs improve practice and service delivery by integrating their specialist knowledge, skill and research evidence (Bryant‐Lukosius et al., ; Lewandowski & Adamle, ), to support evidence‐based practice and improve quality of care (Begley et al., ) and provide safe effective care across a wide range of settings (Newhouse et al., ). CNSs spend varying amounts of time in each component of their role (Colwill et al., ; Kilpatrick et al., ).…”
Section: Introductionmentioning
confidence: 99%